2001
DOI: 10.4049/jimmunol.166.5.3028
|View full text |Cite
|
Sign up to set email alerts
|

Potent Cytolytic Response by a CD8+ CTL Clone to Multiple Peptides from the Same Protein in Association with an Allogeneic Class I MHC Molecule

Abstract: CTL clone 2C recognizes the allogeneic class I MHC molecule Ld in association with peptides derived from α-ketoglutarate dehydrogenase (oxoglutarate dehydrogenase (OGDH)), a ubiquitous intracellular protein. One of these peptides, QLSPFPFDL (QL9), elicits more vigorous cytolytic responses than two previously identified naturally processed peptides with overlapping sequences, LSPFPFDL (p2Ca) and VAITRIEQLSPFPFDL (p2Cb), from OGDH. In this study, we show that QL9 forms a more stable complex with cell surface Ld … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Because prominent recognition of the peptide by the CDR3 region of the TCR would have resulted in altered usage of CDR3 lengths, these results are consistent with the model derived from structural analyses of the molecular interactions involved in direct allorecognition. Indeed, the large number of contacts made by the TCR with the MHC framework (11,12) and the relatively low sensitivity to peptide sequence variations (17,18,43) suggest that direct recognition of nonself-MHC molecules by T cells may be more dependent on interactions of the TCR with the allo-MHC framework determinants than with the peptide itself (20). This low peptide specificity has also been recently suggested by the low contact number between the CDR3 regions of the BM3.3 TCR and an allogeneic MHC-peptide ligand (44).…”
Section: Discussionmentioning
confidence: 99%
“…Because prominent recognition of the peptide by the CDR3 region of the TCR would have resulted in altered usage of CDR3 lengths, these results are consistent with the model derived from structural analyses of the molecular interactions involved in direct allorecognition. Indeed, the large number of contacts made by the TCR with the MHC framework (11,12) and the relatively low sensitivity to peptide sequence variations (17,18,43) suggest that direct recognition of nonself-MHC molecules by T cells may be more dependent on interactions of the TCR with the allo-MHC framework determinants than with the peptide itself (20). This low peptide specificity has also been recently suggested by the low contact number between the CDR3 regions of the BM3.3 TCR and an allogeneic MHC-peptide ligand (44).…”
Section: Discussionmentioning
confidence: 99%
“…The answer is not altogether clear. The number of peptide-MHC complexes required for T lymphocyte recognition varies from several thousand per target cell to as few as one [25,[28][29][30][31][32][33], although weak recognition of other peptides may contribute to the T cell activation process [34]. Some studies have shown a direct correlation between cell surface densities of individual peptide antigens and the magnitude of the immune response against them [35][36][37][38][39], but other studies have shown exactly the opposite [25,27,40].…”
Section: Structural Characteristics Of Peptides Displayed By Mhc Molementioning
confidence: 99%
“…When, however, the target cells expressed L d , background lysis values were higher (ϳ20%) because some naturally occurring (endogenous) cellular peptides associate with L d to form pMHC agonists for 2C cells (10,12). Background lysis values were not subtracted from the reported results.…”
Section: Cytolytic Assaysmentioning
confidence: 99%